Tinseltown : murder, morphine, and madness at the dawn of Hollywood - Mann, William J. (Harper, an imprint of HarperCollinsPublishers, 2014)
Bestselling Hollywood chronicler William J. Mann draws on a rich host of sources, including recently released FBI files, to unpack the story of the enigmatic William Desmond Taylor, the popular president of the Motion Picture Directors Association, and the diverse cast that surrounded him before he was murdered in 1922 -- including three beautiful, ambitious actresses; the ruthless founder of Paramount locked in a struggle for control of the film industry; a grasping stage mother; a devoted valet; and a gang of two-bit thugs, any of whom might have fired the fatal bullet.